Ultrahigh Temperature-Sensitive Silicon MZI with Titania Cladding - Lee, Jong-Moo (Frontiers in Materials, 2015)
We present a possibility of intensifying temperature sensitivity of a silicon Mach-Zehnder interferometer (MZI) by using a highly negative thermo-optic property of titania (TiO2). Temperature sensitivity of an asymmetric silicon MZI with a titania cladding is experimentally measured from +18pm/C to -340 pm/C depending on design parameters of MZI.